Pengembangan Lembar Kerja Siswa Berbasis Pendekatan Saintifik dalam Materi Garis Singgung Lingkaran Kelas VIII - Siti Habibatul Masruroh; Novi Iffatul Azizah; Okta Ridha Kamila; Anas Ma'ruf Annizar (HMPS Tadris Matematika FTIK IAIN Jember, 2021)
Penelitian ini bertujuan untuk mengembangkan lembar kerja siswa menggunakan pendekatan saintifik pada materi garis singgung lingkaran kelas VIII. Penelitian ini merupakan penelitian pengembangan model Thiagarajan yang biasanya dikenal dengan model 4D yaitu meliputi: (1) pendefinisian (define). (2) perancangan (design). (3) pengembangan (develop). (4) penyebaran (disseminate) . Tetapi oleh peneliti di modifikasi menjadi 3D yaitu belum melakukan langkah penyebaran (disseminate) sebab keterbatasannya waktu. Dari penelitian ini skor hasil tes belajar siswa diperoleh 4 atau 80% siswa dinyatakan tidak tuntas dan 2 atau 20% siswa dinyatakan tuntas secara individual, adanya siswa yang masih dibawah KKM dimungkinkan pada waktu pembelajaran siswa masih belum mendalami pokok bahasan serta belum mengerti karena siswa tersebut tidak fokus. Kata Kunci: Lembar Kerja Siswa, Pendekatan Saintifik, Garis Singgung Lingkaran In this study, it is used to explain in developing Student Activity Sheets (LKS) using a scientific approach to the material of tangents to circles. Researchers expect the making of worksheets with a scientific approach to make teaching and learning activities more useful and students are active when teaching and learning takes place using the methods provided in student worksheets so that students can be helped when establishing concepts of understanding and learning methods. This research is known as the 4D model. The research method in scientific-based learning uses worksheets, namely the Thiagarajan development model, usually known as the 4D development model, which is a study that applies four groups, namely (1) Definition. (2) design (design). (3) development (develop). (4) dissemination (disseminated). However, the researchers modified it into 3D, which means that they have not carried out the dissemination step (disseminate) because of time constraints. From this study, the student learning test scores obtained 4 students or 80% of students were declared incomplete and 2 students or 20% of students were declared complete individually, the presence of students who are still below the KKM is possible at the time of learning a student still has not explored the subject and has not understand because the student is not focused. .